Members of German federal parliament: More risk-loving than general population - Moritz Heß; Christian von Scheve; Jürgen Schupp; Gert G. Wagner (DIW Economic Bulletin, 2013)
Politics and business often involve making risky or dangerous decisions whose outcomes can be predicted only with difficulty, if at all. As attitudes toward risks and dangers vary between individuals, it is reasonable that people with different attitudes are active in areas requiring decisions with differing degrees of risk. For example, it has frequently been observed that entrepreneurs are more risk-loving than employees. In late 2011, we surveyed members of the German Bundestag (federal parliament) as to their attitude toward risk (and danger or uncertainty), revealing that they are far more risk-loving than average people; they are even significantly more risk-loving than the self-employed.1 It is possible to take a critical view of the fact that politicians are prepared to assume higher risks than the general population normally would. In this respect, politicians do not represent the population. Yet, we interpret this finding in a positive manner, as a socially rational division of labor between citizens, voters, and politicians in the context of a representative democracy whose institutions limit risk-seeking and power.
Keywords: D71; D78; H11; H70; P16; Z13; 330; political decision-making; risk aversion; German parliament; SOEP